Fzr/Cdh1 Promotes the Differentiation of Neural Stem Cell Lineages in Drosophila - Ly, Phuong Thao; Wang, Hongyan (Frontiers in Cell and Developmental Biology, 2020)
How stem cells and progenitors balance between self-renewal and differentiation is a central issue of stem cell biology. Here, we describe a novel and essential function of Drosophila Fzr/Cdh1, an evolutionary conserved protein, during the differentiation of neural stem cell (NSC) lineages in the central nervous system. We show that Fzr, but not its associating complex named Anaphase Promoting Complex/Cyclosome, promotes the production of neurons from neural progenitors called Ganglion mother cells (GMCs). We also observe a concomitant loss of differentiation factor Prospero expression and ectopic accumulation of mitotic kinase Polo in mutant clones, strongly supporting the impairment of GMC to neuron differentiation. Besides functioning in GMCs, Fzr is also present in NSCs to facilitates the production of intermediate neural progenitors (INPs) from NSCs. Taken together, Fzr plays a novel function in promoting differentiation program during Drosophila NSC lineage development. Given that human Fzr is inactivated in multiple types of human cancers including brain tumors and that Fzr regulates neurotoxicity in various models of neurodegenerative diseases, our study on the role of Fzr turning off proliferation in neuronal cells may provide insight into how Fzr deficit may contribute to human neurodegenerative diseases and tumors.